Analisis Efektivitas Pembiayaan Murabahah dalam Meningkatkan Profitabilitas Bank Syariah di Indonesia - Lisa Efrina (EL-EMIR Institute, 2025)
Murabahah financing is the most dominant financing instrument within Indonesia’s Islamic banking industry and plays a major role in maintaining financial stability. However, its effectiveness in supporting bank profitability requires a comprehensive review based on recent literature. This study aims to analyze the effectiveness of murabahah financing and its contribution to the profitability of Islamic banks in Indonesia by synthesizing research from the past seven years. The method used is a literature study that examines national and international journals, OJK reports, and academic documents related to murabahah mechanisms and Islamic bank financial performance. The findings show that murabahah demonstrates high effectiveness in maintaining margin stability, improving operational efficiency, strengthening productive assets, encouraging financing growth, and ensuring stable cash flows, thus contributing significantly to the profitability of Islamic banks. The study concludes that murabahah serves as a primary foundation for the sustainable financial performance of Islamic banks in Indonesia and should be continuously optimized through improved service quality, product innovation, and enhanced risk management.